40AR/39AR AND 18O/16O STUDIES OF THE CHEGEM ASH-FLOW CALDERA AND THE ELDJURTA GRANITE: COOLING OF TWO LATE PLIOCENE IGNEOUS BODIES IN THE GREATER CAUCASUS MOUNTAINS, RUSSIA - Gazis C.A.; Taylor H.P. Jr.; Lanphere M.; Gurbanov A. (My University, 1995)
Volcanic and intrusive rocks of the Chegem caldera and the nearby Eldjurta (Eldzhurtinskiy) Granite record a late Pliocene episode of silicic magmatism in the north-central Caucasus Mountains. Surface exposures, created by the recent rapid uplift and erosion of the Caucasus Mountains, span a 2 km vertical section of Chegem caldera fill and 1150 m of the Eldjurta Granite; cored mineral-exploration drillholes in the Eldjurta Granite extend the sampling to a depth of 4 km. The unique sampling range available in these two young igneous bodies affords an excellent opportunity to study their denudation and cooling histories, which we examine by means of 40Ar/39Ar and 18O/16O measurements on an extensive sample suite. Total-fusion biotite and sanidine ages from eight Chegem Tuff samples, both intracaldera and outflow, are analytically indistinguishable with a weighted mean of 2.82 ± 0.02 Ma. A cross-cutting granodiorite porphyry intrusion has a sanidine total fusion age of 2.84 ± 0.03 Ma, and whole-rock incremental heating of a post-caldera andesite flow, which caps the caldera fill, yields an age of 2.82 ± 0.02 Ma. Thus, caldera formation and post-caldera resurgence and volcanism all occurred within a very short time (< 50,000 yr). Biotite total-fusion ages of ten Eldjurta Granite samples, including seven from ∼ 500 m intervals in the 4 km deep drillhole, show a systematic linear decrease in age with depth from 1.90 Ma near the roof contact of the granite to 1.56 Ma at a depth of 3700 m. Assuming these ages were set at the same temperature, this age/depth gradient implies an isotherm migration rate of 13 mm/yr between 1.90 and 1.56 Ma. This migration rate is due to a combination of rapid denudation and downward relaxation of isotherms, with cooling rates between 200 and 500°C/Ma during this period. Oxygen isotopic compositions of quartz, K-feldspar, plagioclase and biotite from the drillhole samples below the 800 m depth are fairly uniform and record primary igneous δ18O values with little evidence for subsolidus hydrothermal activity. However, in surface outcrop samples and in the shallowest drillhole sample, mineral δ18O values have been lowered by up to 3‰ by interaction with an external (meteoric-hydrothermal?) fluid. The primary mineral δ18O values of the Eldjurta Granite are distinctly higher than the corresponding phenocryst δ18O values in the Chegem volcanic rocks, indicating that the two bodies evolved as separxate magma batches.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен